2011
DOI: 10.1530/eje-10-0892
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary stalk interruption syndrome in 83 patients: novel HESX1 mutation and severe hormonal prognosis in malformative forms

Abstract: Background: Pituitary stalk interruption syndrome (PSIS) is a particular entity in the population of patients with hypopituitarism. Only rare cases have a known genetic cause. Objectives: i) To compare subgroups with or without extra-pituitary malformations (EPM) in a cohort of PSIS patients to identify predictive factors of evolution, ii) to determine the incidence of mutations of the known pituitary transcription factor genes in PSIS. Study design: We analyzed features of 83 PSIS patients from 80 pedigrees a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
90
3
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(110 citation statements)
references
References 32 publications
10
90
3
7
Order By: Relevance
“…Scholars have gained some knowledge about the regulation of pituitary development; however, the exact mechanism of this process remains unclear. As even a single change in known signaling molecules and transcriptional factors can induce various phenotype and hormone level variations, a greater number of pituitary development-related genes must be investigated further (Reynaud et al, 2011). Previous in vivo studies have demonstrated that the ZBTB20 transcriptional factor, expressed in the pituitary gland, plays a critical role in mouse development (Shillingford et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have gained some knowledge about the regulation of pituitary development; however, the exact mechanism of this process remains unclear. As even a single change in known signaling molecules and transcriptional factors can induce various phenotype and hormone level variations, a greater number of pituitary development-related genes must be investigated further (Reynaud et al, 2011). Previous in vivo studies have demonstrated that the ZBTB20 transcriptional factor, expressed in the pituitary gland, plays a critical role in mouse development (Shillingford et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Ce bilan doit être systématique en l'absence de facteurs de risques ou si l'hypoglycémie persiste au-delà de la durée prévisible. [ ( F i g u r e _ 2 ) T D $ F I G ] néonatale immédiate, 16 % avaient eu des hypoglycémies néonatales et 5 % un ictère non exploré [9]. Malgré ces symptômes, le diagnostic de déficit hypophysaire congénital avait été tardif (âge moyen : 9,6 ans) survenant seulement lorsque le retard de croissance était devenu sévère (taille moyenne : -3,5 AE 1 SDS).…”
Section: Discussionunclassified
“…All coding exons and intron region boundaries of these genes were amplified from genomic DNA as previously described using exon-flanking primers (sequence posted online) [20]. …”
Section: Methodsmentioning
confidence: 99%